First-Principle Calculations on O-Doped Hexagonal Boron Nitride (H-BN) for Carbon Dioxide (CO2) Reduction into C1 Products - Guoliang Liu (Molecules)
With the rapid growth of the world population and economy, the greenhouse effect caused by CO2 emissions is becoming more and more serious. To achieve the “two-carbon” goal as soon as possible, the carbon dioxide reduction reaction is one of the most promising strategies due to its economic and environmental friendliness. As an analog of graphene, monolayer h-BN is considered to be a potential catalyst. To systematically and theoretically study the effect of O doping on the CO2 reduction catalytic properties of monolayer h-BN, we have perform a series of first-principle calculations in this paper. The structural analysis demonstrates that O preferentially replaces N, leading to decreasing VBM of monolayer h-BN, which is conducive to improving its capability for CO2 reduction. The preferential CO2 adsorption sites on monolayer h-BN before and after O doping are the N-t site and B-t site, respectively. O doping increases the adsorption strength of CO2, which is favorable in the further hydrogenation of CO2. During the conversion of CO2 into CO and HCOOH via a two-electron pathway and CH3OH and CH4 via a six-electron pathway, O doping can reduce the energy barrier of the rate determining step (RDS) and change the key steps from uphill reactions to downhill reactions, thus increasing the probability of CO2 reduction. In conclusion, O(N)-doped h-BN exhibits the excellent CO2 reduction performance and has the potential to be a promising catalyst.